1997
DOI: 10.1002/(sici)1098-2396(199709)27:1<1::aid-syn1>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of d‐amphetamine effects on the binding of dopamine D‐2 receptor radioligand, 18F‐fallypride in nonhuman primates using positron emission tomography

Abstract: We have investigated the ability of dopamine to compete with the binding of the high affinity dopamine D2 receptor positron emission tomography (PET) radioligand, 18F-fallypride. In vitro dissociation of 18F-fallypride with dopamine in rat striatal homogenates exhibited a dissociation rate, k(off), of 1.76 x 10(-2) min(-1) while the association rate constant, k(on), was found to be 5.30 x 10(8) M(-1) min(-1). This resulted in a dissociation constant, K(D) of 33 pM for 18F-fallypride. For in vivo studies, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…We have previously shown that binding of 18 F-fallypride is not significantly altered in reserpinized rats compared to control rats, suggesting that basal levels of dopamine has little affect on 18 F-fallypride binding to D-2 receptors (Mukherjee et al 1997). However, when the concentration of dopamine is increased by pharmacological challenges of d-amphetamine, displacement of 18 F-fallypride is observed.…”
Section: Can Endogenous Dopamine Affect D-2 Occupancy By Clozapine?mentioning
confidence: 90%
“…We have previously shown that binding of 18 F-fallypride is not significantly altered in reserpinized rats compared to control rats, suggesting that basal levels of dopamine has little affect on 18 F-fallypride binding to D-2 receptors (Mukherjee et al 1997). However, when the concentration of dopamine is increased by pharmacological challenges of d-amphetamine, displacement of 18 F-fallypride is observed.…”
Section: Can Endogenous Dopamine Affect D-2 Occupancy By Clozapine?mentioning
confidence: 90%
“…DA synthesis was assessed using FMT as a PET tracer (DeJesus, Endres, Shelton, Nickles, & Holden, 1997). The tracer used to assess D 2 receptors was FAL, an F-18-labeled raclopride analog developed by Mukherjee et al (1997); 5 mCi in 1-5 ml normal saline of either FAL or FMT were administered as an intravenous bolus and a dynamic sequence of images over 90 min, including a total of 13 frames with duration increasing from 2 to 10 min was collected. At the end of scanning, the animals were extubated, allowed to awaken, and then returned to the animal care facility.…”
Section: Pet Proceduresmentioning
confidence: 99%
“…The striatum is rich in dopaminergic innervation and is part of the basal ganglia thalamo-cortical loop involved in behavioral inhibition (Casey, 2001 (Mukherjee et al, 1997;Schneider et al, 2005).…”
mentioning
confidence: 99%
“…The striatal uptakes of [ Olsson et al, 1999;Fujita et al, 1999), making estimation of striatal DA D 2 /D 3 receptor levels difficult. [ 18 F]fallypride is a benzamide with very high-affinity for DA D 2 /D 3 receptors, which has been used to visualize and quantify levels of striatal and extrastriatal DA D 2 /D 3 receptors using positron emission tomography (PET) (Mukherjee et al, 1999Rieck et al, 2004 (Mukherjee et al, 1997;Kessler et al, 1991;Olsson et al, 1999Olsson et al, , 2004Christian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%